Ottawa materials, Selected materials, 1676-1930, on Indian linguistics - Unknown
Part of a collection comprised of religious and linguistic materials in various Native American languages. Many were written by Jesuit missionaries of New France. These particular items relate to the Ottawa (Odawa) language and include prayers, hymns, and catechisms. Originals at the Archives de l'Archeveche de Quebec and Universite Laval, Seminaire de Quebec.